Studying the effect of the standard of living on the quality of academic achievement for higher education students using artificial intelligence (Fuzzy inference) - A.Elbhilil, Fatma; A. Elbhilil, Nagah (Journal of Pure & Applied Sciences, 2023)
This study aims to study the effect of the standard of living on the quality of overt achievement of higher education students by using artificial intelligence represented by fuzzy logic, given that it has the ability to deal with vague information, which is difficult to estimate. In this study, Mamdani fuzzy inference was used to determine the relationship between the standard of living and between the quality of the academic achievement of the students of the College of Science for the academic year 2021-2022 AD to change the linguistic values into digital values that can be measured724. A random sample of the total number of respondents1473, so that the obtained results were projected on the entire sample community 90, where the study determined the level of quality of educational attainment, which was set at 50%. Artificial intelligence (fuzzy inference) technology, as it is of an average level, as in reality, and recommendations for the use of modern technologies, including artificial intelligence (fuzzy) in obtaining information about students in the college, whether their academic level or otherwise.